A katasztrófa meghatározása - Molnár, András (METSZETEK Társadalomtudományi Folyóirat, 2024)
Marie Aronsson-Storrier – Rasmus Dahlberg (eds.) (2022): Defining Disaster. Edward Elgar, Cheltenham, 264 oldal